2012
DOI: 10.1111/j.1751-7915.2012.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in the rhizosphere of maize and the surrounding carbonate‐rich bulk soil

Abstract: Maize represents one of the main cultivar for food and energy and crop yields are influenced by soil physicochemical and climatic conditions. To study how maize plants influence soil microbes we have examined microbial communities that colonize maize plants grown in carbonate-rich soil (pH 8.5) using culture-independent, PCR-based methods. We observed a low proportion of unclassified bacteria in this soil whether it was planted or unplanted. Our results indicate that a higher complexity of the bacterial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
59
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 90 publications
15
59
1
2
Order By: Relevance
“…Chao1 estimator value for S. saponaria rhizosphere was 10,790.46. The Shannon and Simpson indexes were 7.237 and 0.0027, respectively, for the Sapindus rhizosphere (present work) and 3.42 and 0.059, respectively, for maize rhizosphere (García-Salamanca et al, 2013), indicating that the bacterial community in the S. saponaria rhizosphere was more complex than the maize rhizosphere. Similar to the observations of García-Salamanca et al (2013), the most predominant 16S rRNA gene sequences in the S. saponaria rhizosphere were those of Actinobacteria, Acidobacteria, and Proteobacteria.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Chao1 estimator value for S. saponaria rhizosphere was 10,790.46. The Shannon and Simpson indexes were 7.237 and 0.0027, respectively, for the Sapindus rhizosphere (present work) and 3.42 and 0.059, respectively, for maize rhizosphere (García-Salamanca et al, 2013), indicating that the bacterial community in the S. saponaria rhizosphere was more complex than the maize rhizosphere. Similar to the observations of García-Salamanca et al (2013), the most predominant 16S rRNA gene sequences in the S. saponaria rhizosphere were those of Actinobacteria, Acidobacteria, and Proteobacteria.…”
Section: Discussionmentioning
confidence: 43%
“…The soil microbial biomass carbon and nitrogen, and nitrification, are also significantly positively correlated to the soil pH (Kemmitt et al, 2006). The index values for the 2660 OTUs of S. saponaria rhizosphere, at 3% distance sequence dissimilarity, were much higher than the values obtained by García-Salamanca et al (2013), who studied the bacterial diversity of maize rhizosphere. They obtained less than 60 OTUs from a relatively high pH, carbonate-rich soil typical of Southern Spain.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…SI_7). Another study conducted in the carbonate-rich soil (pH 8.5) using 16S rRNA clone library analysis showed that Pseudomonas and Lysobacter genera constituted 45% of the total bacterial abundance in the maize rhizosphere (García-Salamanca et al, 2013). Though exact mechanisms for such differences are not completely understood, because these studies were all conducted on different soil types, it is likely that soil type may be one of the most important environmental variables influencing the structure of the maize root-inhabiting bacterial community at low taxonomic levels (Berg and Smalla, 2009;Castellanos et al, 2009;Garbeva et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Gammaproteobacteria, which was abundant in rhizosphere samples, and respond chemotactically to exudates and are efficient in the utilization of plants exudate products (GARCÍA-SALAMANCA et al, 2012). The class Alphaproteobacteria presented a significant enrichment in the 5-year soybean rhizosphere.…”
Section: Specific Groups Of Proteobacteria Contain Plant-growth-promomentioning
confidence: 96%